Strategi Pengelolaan Timbulan Sampah Organik Melalui Konversi Produksi Kompos di Kabupaten Keerom Papua - Kabelen, Floriana; Tanjung, Rosye H.R.; Suharno, Suharno (Jurnal Biologi Papua, 2024)
Organic waste, characterized by its high water content and rapid decomposition, poses environmental challenges and risks of disease outbreaks if not managed effectively. One promising solution is converting organic waste into compost. This study aims to quantify waste generation by weight and type while exploring composting as an alternative management strategy in Yuwanain Village, Arso District, Keerom Regency. The research employed methods including waste sampling, measurement, and data analysis, with the study area focused on Yuwanain Village. Over eight days, 255.25 kg of waste was collected, comprising 133.5 kg of organic waste and 116.75 kg of inorganic waste. Processing 133.5 kg of organic waste yielded approximately 20 kg of compost, representing 15% of the total organic waste weight. Overall, the conversion of organic waste into compost reduced waste generation by 53%. This composting potential offers a sustainable alternative for producing organic fertilizer, which could significantly contribute to agricultural systems in Keerom, Papua.